2013
DOI: 10.2474/trol.8.179
|View full text |Cite
|
Sign up to set email alerts
|

Study of Belt Friction with Three Times Wrapping Condition

Abstract: Theoretical study was carried out to investigate the frictional property of belt wrapped three times around a circular shaft. A belt equation of fractional expression was derived. The self-locking mechanism was investigated theoretically by the equation. The discriminant of self-locking condition was clarified. The necessary conditions for self-locking are µ b < µ and sufficient wrapping angle of the belt, where µ is the coefficient of friction between the belt and shaft and µ b is the coefficient of friction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Imado found the self-locking property of the belt in the course of his study and showed the theoretical self-locking condition for two and three times wrapping condition of belt (Imado, 2008;Imado, et al, 2013a). He devised a one-way clutch by utilizing the self-locking property of belt (Imado, et al, 2010;Imado, et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Imado found the self-locking property of the belt in the course of his study and showed the theoretical self-locking condition for two and three times wrapping condition of belt (Imado, 2008;Imado, et al, 2013a). He devised a one-way clutch by utilizing the self-locking property of belt (Imado, et al, 2010;Imado, et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…The calculation method has to be verified so that it satisfies the static equilibrium of force and moment to an entire body. Equations were derived by which the frictional force of a belt wrapped two and three times around a cylindrical surface can be calculated [3,4]. By using these equations, the self-locking condition of belt was clarified.…”
Section: Introductionmentioning
confidence: 99%